Improved pain and joint function with absorbable pins and mini external fixator distraction in Freiberg disease: a 41-month follow-up study - Lai, Zhibin; Lin, Yuying; Zhu, Yongzhan; Yang, Kangyong; Lai, Junhui; Zhang, Hongning; Zou, Baoli; Cheng, Chen; Shen, Guodong (Frontiers in Surgery, 2025)
PurposeFreiberg disease, a relatively uncommon condition affecting the metatarsal head, often requires surgical intervention when conservative treatments fail. Using absorbable pins combined with mini external fixator distraction, we aimed to assess the efficacy of dorsal closing wedge osteotomy (DCWO) in the treatment of Freiberg disease.MethodsThis retrospective study analyzed data from 18 patients with Freiberg disease treated from June 2016 to June 2020. Patients were treated with DCWO using absorbable pins combined with mini external fixator distraction. Clinical and functional outcomes included Visual Analogue Scale (VAS) for pain, American Orthopaedic Foot & Ankle Society Lesser Metatarsophalangeal-Interphalangeal (AOFAS-LMI) score, and active sagittal-plane ROM of the second MTP measured with a specific goniometer. Radiologic assessment used weight-bearing AP foot radiographs to quantify second-metatarsal shortening (normalized to first-metatarsal length). The progression of MTP arthritis was a focus of assessment. Assessments were performed preoperatively, at 6 months, 1 year, and final follow-up. Complications were systematically documented.ResultsCompared to preoperative values, significant improvements were observed in VAS scores, AOFAS-LMI scores, and metatarsophalangeal joint ROM over an average follow-up duration of 41.0 ± 17.0 (0.5–20) months. Specifically, VAS scores decreased from 5 (4, 5) to 0.5 (0, 1), while AOFAS-LMI scores increased from 68.3 ± 5.0 to 92.5 ± 2.9. Furthermore, dorsiflexion improved from (15.83 ± 6.4)° to (32.7 ± 4.8)°, plantarflexion increased from (13.9 ± 6.1)° to (29.3 ± 4.3)°, and the total ROM increased from (29.7 ± 9.0)° to (62.5 ± 6.9)°. All changes were statistically significant (P < 0.01). The average metatarsal shortening was 2.96 ± 0.70 (1.8–4.1) mm. The incidence of pin-related infections associated with external fixators was 5.6%. No radiographic or clinical evidence of osteoarthritis was observed in the metatarsophalangeal joint at the final follow-up.ConclusionDCWO with absorbable pins and mini external fixator distraction is safe and effective for treating Freiberg disease. It enables early functional exercise, avoids the need for surgical removal of internal implants, and potentially delays the progression of arthritis with distraction techniques.